ECONOMIC NUTRITIONAL REQUIREMENTS FOR IRAQI AWASSI SHEEP - S.A. Al-Tekrity , S.; K. Al-Murani‎, W. (The Iraqi Journal of Veterinary Medicine, 2024)
This study was performed to define the best nutritional level expressed according to Morrison feeding standard 80%, 100% and 120% of these standards were given to three groups of awassi lumbs. Results indicated the superiority of the 120% level in reaching the slaagter weight (45 Kg).The experiment also reflected that digestibility in goats is better than that in sheep.